Geographic, Subject, and Authorship Trends among LMIC-based Scientific Publications in High-impact Global Health and General Medicine Journals: A 30-Month Bibliometric Analysis - Marium Ghani; Rowan Hurrell; Avelino C. Verceles; Michael T. McCurdy; Alfred Papali (Springer, 2020)
The globalization of medical research and global health's increasing popularity worldwide have resulted in greater geographic, ethnic, and socioeconomic diversity of studies published in the scientific literature. Yet the geographic distribution, authorship representation, and subject trends among Low-/Low-Middle-Income Country (LIC/LMIC)-based scientific publications remain largely unknown. This analysis assesses these gaps in knowledge. We performed a comprehensive bibliometric analysis of all scientific articles published between January 2014 and June 2016 in the four most prominent general medicine and five most prominent general global health journals based on impact factor. The African region, containing 24% of the global LIC/LMIC population, accounted for 49.9% of all publications. Corresponding authors with either exclusive or joint appointment to a LIC/LMIC institution were present in 26.2% of all included articles. Over one-quarter (28.8%) of all publications did not list a local author. Nearly two-thirds (62.1%) of articles published in global health journals and roughly half (52.4%) in general medicine journals involved infectious diseases. Non-HIV infectious disease studies were by far the most frequent subject areas across all journals. The trends identified in this study may help to inform the evolution and prioritization of future research efforts, thereby allowing global health to remain truly global.